Abstract of: Interlocking glass spiral as building structure of the watch museum “La Maison des Fondateurs” - Josua Villiger (Challenging Glass Conference, 2018)
La Maison des Fondateurs in Le Brassus Switzerland is going to represent the watch making manufacture Audemars Piguet. Audemars Piguet stands for the finest quality, precision as well as innovation based on traditional watchmaking expertise and craftsmanship. La Maison des Fondateurs has been developed from a competition proposal to the execution project by the architects BIG – Bjarke Ingels Group. The created interlocking all glass spiral evolves the building volume out of the rough, natural landscape providing a perfect linear museum path for the building program. Despite the severe loading and weather conditions, inspired by the high values of Audemars Piguet the project team designed the building to the technical limits. The curved and very large insulated façade glass units as well as the curved glass partition walls of the interlocking glass spiral are forming the load bearing structure. All vertical and horizontal loads are transferred by these glass components making solid columns and shear wall obsolete. The article reflects the close collaboration of the designers, engineers, specialist contractor and industry. The global structural concept, transfer of the concentrated point loading into the curved structural glass element, testing procedures as well as the structural bonding beyond standards and the context of energy efficiency are discussed and elaborated.